Strategi Guru dalam Pembelajaran Aqidah Akhlak Di MTs Negeri 2 Balikpapan - Mahmudah, Imil; Jannah, Fathul; Basith, Abdul (Borneo Journal of Islamic Education, 2022)
MTs Negeri 2 Balikpapan is a school that plays an important role in learning Aqidah Akhlak which has included in the school's mission, namely "instilling faith, piety and noble character through religious practice". Education can be said as a series of learning processes to become human beings who continue to grow physically, mentally and spiritually. The aim of the study was to determine the teacher's strategies for Aqidah Akhlak at MTs Negeri 2 Balikapapan. This type of research is qualitative research. Sources of data are school principals, deputy heads of curriculum, Aqidah Akhlak teachers and students of MTs Negeri 2 Balikpapan with data collection techniques using observation, interviews and documentation. The data validity technique in this study uses source triangulation and technical triangulation. The data analysis technique used is data reduction, data presentation, data verification. The results of this study indicate that the teacher's strategy in learning Aqidah Akhlak at MTs Negeri 2 Balikpapan is in compiling the teaching stages of the teacher compiling learning objectives by including all domains of cognitive, affective and psychomotor aspects, basic competencies and indicators that have been prepared by the teacher is to determine operational verbs that can be observed and measured. The media/tool ​​used by the teacher is PPT, the learning video of this media is in accordance with the learning objectives to be achieved while the learning resources compiled are books, the internet and the environment using this adds broad and deep student insight. The evaluation compiled is an authentic assessment assessment. The learning model uses a discovery learning model and a problem based learning model.